HYPOPITUITARISM FOLLOWING TRAUMATIC BRAIN INJURY: DETERMINING FACTORS FOR DIAGNOSIS - CASANUEVA, FELIPE F; Castro, Ana I.; Fernandez-Rodriguez, Eva; Bernabeu, Ignacio; Kelestimur, Fahrettin (Frontiers in Endocrinology, 2011)
Neuroendocrine dysfunction, long recognised as a consequence of traumatic brain injury (TBI), is a major cause of disability that includes physical and psychological involvement with long-term cognitive, behavioural and social changes. There is no standard procedure regarding at what time after trauma the diagnosis should be made. Also there is uncertainty on defining the best methods for diagnosis and testing and what types of patients should be selected for screening. Common criteria for evaluating these patients are required on account of the high prevalence of TBI worldwide and the potential new cases of hypopituitarism.